The 2dF Galaxy Redshift Survey: Higher-order galaxy correlation functions - Croton, D; Gaztañaga, E; Baugh, C; Norberg, P; Colless, M; Baldry, L; Bland-Hawthorn, J; Bridges, T; Cannon, R; Cole, S; Collins, C; Couch, W; et al. (2004)
We measure moments of the galaxy count probability distribution function in the Two-degree Field Galaxy Redshift Survey (2dFGRS). The survey is divided into volume-limited subsamples in order to examine the dependence of the higher-order clustering on galaxy luminosity. We demonstrate the hierarchical scaling of the averaged p-point galaxy correlation functions, ξ̄ p, up to p = 6. The hierarchical amplitudes, S p = S 2S p-1, are approximately independent of the cell radius used to smooth the galaxy distribution on small to medium scales. On larger scales we find that the higher-order moments can be strongly affected by the presence of rare, massive superstructures in the galaxy distribution. The skewness S 3 has a weak dependence on luminosity, approximated by a linear dependence on log luminosity. We discuss the implications of our results for simple models of linear and non-linear bias that relate the galaxy distribution to the underlying mass.